Physical Activity, Fibrinogen Plasma Level and Gene Polymorphisms in Postmenopausal Women - Rauramaa, Rainer; Väisänen, Sari; Nissinen, Aulikki; Rankinen, Tuomo; Penttilä, IIkka; Saarikoski, Seppo; Tuomilehto, Jaakko; Gagnon, Jacques; Pérusse, Louis; Bouchard, Claude (Thrombosis and Haemostasis, 1997)
The relations between habitual physical activity (PA), fibrinogen gene polymorphisms and plasma fibrinogen were investigated in 191 postmenopausal women. Subjects who reported PA at least 4 times/ week had lower fibrinogen level (3.19 g/1; 95% Cl 3.10; 3.27) than women reporting PA 2-3 times/week (3.43 g/1; 3.29; 3.58) or sedentary subjects (3.64 g/1; 3.33; 3.94). There were no differences in plasma fibrinogen across the α-fibrinogen (Rsal, TaqI) or (β-fibrinogen (Mnll, Bell, Hindlll) genotypes, the frequencies of which were in a Hardy- Weinberg equilibrium. An interaction between Rsal, which was in complete linkage disequilibrium with TaqI, and PA on plasma fibrinogen was observed, even after adjustments for BMI, smoking and medication (p = 0.024). Among women homozygous for the common Rsal allele, the physically most active had lower fibrinogen level (p <0.001) compared to the physically less active subjects. These results suggest that, in postmenopausal women, the relation between physical activity and plasma fibrinogen is modulated by genetic variation in the α-fibrinogen gene.